Demography, Capital Flows and Asset Allocation over the Life-cycle - Katja Mann; Margaret Davenport (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the effect of population aging on portfolio choice, asset prices and international asset trades. In a multi-period OLG model, we analyze how an increase in longevity or a decrease in fertility in a country affects the demand for safe and risky assets. In a closed economy, given a fixed supply, the riskfree rate falls and the risk premium rises, because retirees prefer to hold a larger share of safe assets in their portfolio than working-age households. In a financially integrated world, countries with more extreme demographic trends export risky assets and import safe assets. We quantify these effects for the United States.
Keywords: G11; G15; J11; 330